2013
DOI: 10.1890/12-1366.1
|View full text |Cite
|
Sign up to set email alerts
|

Life‐history traits and landscape characteristics predict macro‐moth responses to forest fragmentation

Abstract: How best to manage forest patches, mitigate the consequences of forest fragmentation, and enable landscape permeability are key questions facing conservation scientists and managers. Many temperate forests have become increasingly fragmented, resulting in reduced interior forest habitat, increased edge habitats, and reduced connectivity. Using a citizen science landscape-scale mark-release-recapture study on 87 macro-moth species, we investigated how both life-history traits and landscape characteristics predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(150 citation statements)
references
References 49 publications
10
138
1
1
Order By: Relevance
“…These figures alone indicate that hedgerows may be key habitat features for macromoths within agricultural landscapes. This result supports the findings from previous studies that hedgerows are important habitat features for invertebrates within agricultural landscapes and more specifically for butterflies and moths (Maudsley 2000;Dover 1990;Merckx et al 2010b;Slade et al 2013). Other researchers have found that butterflies may be using hedgerows as wildlife corridors and these results suggest that moths are also using hedges in a similar manner nocturnally (Dover 1990).…”
Section: Discussion Moth Abundance and Hedgerow Proximitysupporting
confidence: 91%
See 3 more Smart Citations
“…These figures alone indicate that hedgerows may be key habitat features for macromoths within agricultural landscapes. This result supports the findings from previous studies that hedgerows are important habitat features for invertebrates within agricultural landscapes and more specifically for butterflies and moths (Maudsley 2000;Dover 1990;Merckx et al 2010b;Slade et al 2013). Other researchers have found that butterflies may be using hedgerows as wildlife corridors and these results suggest that moths are also using hedges in a similar manner nocturnally (Dover 1990).…”
Section: Discussion Moth Abundance and Hedgerow Proximitysupporting
confidence: 91%
“…It is likely that factors such as size, mobility and resource requirements of moth species will have an impact on the behavioural ecology of a species and therefore its response to linear landscape features. Such varied responses have already been observed with moth species to hedgerow trees (Merckx et al 2010b;Slade et al 2013). …”
Section: Discussion Moth Abundance and Hedgerow Proximitysupporting
confidence: 52%
See 2 more Smart Citations
“…Based on studies of animals and plants in urban ecosystems, we expected that species richness would be lower in street medians than in city parks. Additionally, we expected the composition of microbial communities to be distinct in the two habitat types because previous studies have shown that persisting in high-stress habitats and/or maintaining viable populations in small habitat patches can be strongly influenced by speciesspecific traits (Schleicher et al, 2011;Slade et al, 2013;Concepción et al, 2015).…”
Section: Introductionmentioning
confidence: 99%